PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PERUSAHAAN PERBANKAN PERIODE 2016 – 2019 - utami, anis; Anita Wijayanti; Endang Masitoh (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to find out about the influence of ROA, ROE, size and FAR on thecapital structure of the company. The population in this study is banking companieslisted on the Indonesia Stock Exchange for the period 2016-2019 as many as 42companies and 121 samples. this study used multiple linear regressions as ananalysis aalat. The results of hypothesis testing show that ROA affects the capitalstructure of the company, this can be interpreted that the higher roa owned by thecompany, the lower the capital structure of the company. Hypothesis 2 testing showsthat ROE affects the company's capital structure. It can be concluded that the higherthe ROE owned by the company, the higher the capital structure of the company. Thetest results showed that size and FAR had no effect on the capital structure. Thismeans that the size and FAR cannot affect the up/down capital structure of thecompany..